2017
DOI: 10.1007/s00464-017-5672-0
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of the endoscopic duodenal–jejunal bypass liner prototype in severe or morbidly obese subjects implanted for up to 3 years

Abstract: This study shows significant and sustained weight loss after 3 years of treatment with the new DJBL. However, the high frequency and severity of AEs preclude the use of this prototype for periods longer than 1 year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 16 publications
1
24
0
Order By: Relevance
“…The desired biological effects stabilize after the first 12 months after implantation and DJBL removal results in weight regain and loss of glycemic control. This accords with data from a study with DJBL dwelling times up to 3 years [6]. A possible reason for the observed stabilization during dwelling time might be that the DJBL is tolerated better over time, patients have less abdominal complaints, early satiety diminishes, and therefore intake is increased.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The desired biological effects stabilize after the first 12 months after implantation and DJBL removal results in weight regain and loss of glycemic control. This accords with data from a study with DJBL dwelling times up to 3 years [6]. A possible reason for the observed stabilization during dwelling time might be that the DJBL is tolerated better over time, patients have less abdominal complaints, early satiety diminishes, and therefore intake is increased.…”
Section: Discussionsupporting
confidence: 88%
“…The cohort study of Quezada et al describes an early removal rate of 86% before 36 months. In total, 29% of the early removals were due to AEs and 55 DJBL-related SAEs were observed in 80 patients of which three were hepatic abscess [6]. This suggests that all patients are at risk to develop (S)AEs during the complete dwelling time.…”
Section: Discussionmentioning
confidence: 99%
“…A second-generation EndoBarrier device with a 1 mm increase in barb length was trialed in 80 patients in Chile. The subjects initially consented to the implant for one year but were then given the opportunity to keep the device in for up to 3 years if tolerated [ 40 ]. The percentage excess weight losses in the complete population at 52 weeks (71 patients), 104 weeks (40 patients), and 156 weeks (11 patients) were 44 ± 16, 40 ± 22, and 39 ± 20, respectively ( p < 0.001).…”
Section: Future Developmentsmentioning
confidence: 99%
“…Future research should be focused on reimplantation strategies or a device that could remain in situ for longer, thereby providing a more permanent solution. A recent study already demonstrated implantation of a new prototype for up to 3 years in two obese subjects with T2DM, but high frequency and severity of AE's still preclude the use of the device for a period longer than 1 year [11]. Efforts are made to kick start further development to combat these issues.…”
Section: Efficacy and Safety Profilementioning
confidence: 99%